2023
DOI: 10.1002/chem.202300443
|View full text |Cite
|
Sign up to set email alerts
|

Cover Feature: Green and Fast Strategies for Energy‐Efficient Preparation of the Covalent Organic Framework TpPa‐1 (Chem. Eur. J. 15/2023)

Abstract: Nontoxic and energy‐efficient COF synthesis: Covalent organic framework TpPa‐1 has been successfully obtained in a microwave‐assisted hydrothermal synthesis, replacing the traditional organic‐based solvent with water and reducing reaction times from several days to 30 minutes. High‐temperature hydrothermal synthesis resulted in higher BET specific surface areas (compared to traditional solvothermal processes), improved material yields, and excellent textural properties. More information can be found in the Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The so‐made COFs displayed good crystallinity, porosity, and high yield and avoided harsh conditions like the usage of high temperatures and dangerous solvents. In another study by Visus et al., three production processes for COFs were studied and compared with the aim of setting up the best hopeful one in a fast, sustainable, and green way using water as the green solvent and non‐toxic solvent for washing [67] . Indeed, substituting hazardous solvents with greener alternatives can reduce costs and toxicity.…”
Section: Green Solvents To Prepare Cofsmentioning
confidence: 99%
See 1 more Smart Citation
“…The so‐made COFs displayed good crystallinity, porosity, and high yield and avoided harsh conditions like the usage of high temperatures and dangerous solvents. In another study by Visus et al., three production processes for COFs were studied and compared with the aim of setting up the best hopeful one in a fast, sustainable, and green way using water as the green solvent and non‐toxic solvent for washing [67] . Indeed, substituting hazardous solvents with greener alternatives can reduce costs and toxicity.…”
Section: Green Solvents To Prepare Cofsmentioning
confidence: 99%
“…In another study by Visus et al, three production processes for COFs were studied and compared with the aim of setting up the best hopeful one in a fast, sustainable, and green way using water as the green solvent and non-toxic solvent for washing. [67] Indeed, substituting hazardous solvents with greener alternatives can reduce costs and toxicity. The outcomes showed that COFs can be prepared via microwave hydrothermal production with crystallinity, texture, and morphology like those gained by both mechano-chemical conventionalheating hydrothermal.…”
Section: Water Solventmentioning
confidence: 99%